2022
DOI: 10.1186/s12906-022-03629-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Suppression of NF-κB signaling by ECN in an arthritic model of inflammation

Abstract: Background The 7β-(3-ethyl-cis-crotonoyloxy)-1α-(2-methylbutyryloxy)-3,14-dehydro-Z-notonipetranone (ECN), a sesquiterpenoid isolated from the Tussilago farfara Linneaus (Asteraceae), was evaluated against acute Carrageenan and chronic complete Freund’s adjuvant (CFA)-induced arthritis in mice. Methods Acute and chronic arthritis were induced by administering Carrageenan and CFA to the intraplantar surface of the mouse paw. Edema, mechanical allody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have demonstrated the importance of oxidative-antioxidative balance in thrombosis and the correlation between oxidative stress imbalance and thrombosis [ 21 , 22 ]. It has also been shown that k-carrageenan is a pro-inflammatory compound widely used in experimental animal models [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of oxidative-antioxidative balance in thrombosis and the correlation between oxidative stress imbalance and thrombosis [ 21 , 22 ]. It has also been shown that k-carrageenan is a pro-inflammatory compound widely used in experimental animal models [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-1β augments the TLR-7 activity on helper T-cells and worsens the NF-κβ mediated immune activity as a feedback response 21 . Furthermore, the constitutive production of NF-κβ is also the culprit for psoriatic pathogenesis as well as other anomalies 60 , 83 . This activation of the IMQ independent inflammation pathway was not observed with IMQ-nTES gel as evident by markedly reduced expression of constitutive NF-κβ, helper CD4 + T cells, IL-1β and IL-17A.…”
Section: Discussionmentioning
confidence: 99%
“…IMQ-nTES gel was, however, found to be comparatively safer than conventional ALDARA cream, owing to optimal stimulation of cutaneous immune cells, non-constitutive NF-κβ, and cytokines synthesis. According to the study published by Li et al, the constitutive (overexpressed) NF-κβ has resulted in the pathogenesis of Hepatocellular carcinoma 83 . Basically, the NF-κβ can be beneficial as well as harmful and can be referred to as a double-edged sword.…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) was measured to estimate lipid peroxidation in the brain and spinal cord (L4‐L6), as described previously (Ali et al, 2020; Khan, Khan, Shal, et al, 2022a; Khan, Khan, Khan, Shal, et al, 2022b; Khan, Khan, Zafar, et al, 2022e; Khan, Wang, et al, 2022c; Khan, Zhang et al, 2022d). The quantitative measurement of MDA in the tissue homogenate was an index of lipid peroxidation.…”
Section: Methodsmentioning
confidence: 99%
“…Percentages were used to express the results. The procedure was carried out as directed by the manufacturer (Khan et al, 2013a; Khan, Khan, Khan, Shal, et al, 2021d; Khan, Khan, Shal, et al, 2022a; Khan, Khan, Khan, Shal, et al, 2022b; Khan, Khan, Zafar, et al, 2022e; Khan, Wang, et al, 2022c; Khan, Zhang et al, 2022d).…”
Section: Methodsmentioning
confidence: 99%